2011
DOI: 10.1016/j.ultramic.2010.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative atom probe analysis of carbides

Abstract: Compared to atom probe analysis of metallic materials, the analysis of carbide phases results in an enhanced formation of molecular ions and multiple events. In addition, many multiple events appear to consist of two or more ions originating from adjacent sites in the material. Due to limitations of the ion detectors measurements generally underestimate the carbon concentration. Analyses using laser-pulsed atom probe tomography have been performed on SiC, WC, Ti(C,N) and Ti(2)AlC grains in different materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(118 citation statements)
references
References 24 publications
5
111
2
Order By: Relevance
“…On the other hand, we have previously shown that the agreement between experiment and calculation is satisfactory at the C K edge, for which the octahedral site leads to an overall more isotropic chemical bonding and the Muffin-Tin approximation thus adapted. To end, let us mention that, like at the C K edge, we do not include any disorder in the FEFF calculation, disorder that is known to be significant: a corrugation of Al planes could also contribute to increase the disagreement in the case of the Al K edge [67,4].…”
Section: Al-k Xanesmentioning
confidence: 99%
“…On the other hand, we have previously shown that the agreement between experiment and calculation is satisfactory at the C K edge, for which the octahedral site leads to an overall more isotropic chemical bonding and the Muffin-Tin approximation thus adapted. To end, let us mention that, like at the C K edge, we do not include any disorder in the FEFF calculation, disorder that is known to be significant: a corrugation of Al planes could also contribute to increase the disagreement in the case of the Al K edge [67,4].…”
Section: Al-k Xanesmentioning
confidence: 99%
“…The detection efficiency is usually 30-60%, depending on instrument type, and it is the same for all elements, thus giving excellent compositional accuracy, without the need of standard samples and element specific calibration. In some cases, though, the accuracy of concentration measurements is significantly reduced, for example when analyzing carbides [1], nitrides [2], silicides [3] or semiconductors [4]. In the case of carbides, the main reason why the obtained carbon concentration is usually too low is the limited capability of the detector to register all ions resulting from the same pulse.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases it is possible to use only isotopes of low abundance for quantification, as the probability is low that more than one such ion from a single pulse hit the detector. This has been demonstrated for the analysis of carbides, using the 13 C isotope [1]. To some extent it is possible to decrease the fraction of multiple events by changing the analysis conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The quantitative analysis is based on isotope distributions of different ions of relevant atom types. 24 The quantitative APT analysis of C atoms is based on ions detected at 6, 6.5, 12 and 13 Da, plus all ions which exceeded the expected Ti level at 24 Da (as two C ions).…”
Section: Methodsmentioning
confidence: 99%